2022
DOI: 10.3390/ejihpe12010005
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Emotional Exhaustion Scale (ECE) in Chilean Higher Education Students

Abstract: The main objective of this study was to estimate the psychometric properties of the Emotional Fatigue Scale (ECE) in a sample of 1308 Chilean university students and confirm the unifactorial structure of the scale. Exploratory and confirmatory factor analyses were carried out. The ECE assessment had an internal consistency of 0.893 (Cronbach’s Alpha). An exploratory factor analysis with Varimax rotation and a confirmatory analysis were performed, obtaining the factor that explains 52.3% of the variance. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Likewise, domestic violence has been identified as a predictor of depression ( 35 ). Moreover, emotional exhaustion has been higher in women than men during the COVID-19 pandemic ( 32 , 36 , 37 ), which has been directly associated with the increase or onset of depression ( 38 ). In addition, the mental health status of women in Latin America depends on several social determinants: unequal access to education and work and their benefits, as well as exposure to violence and lack of adequate reproductive health, which affect their psychological well-being ( 39–41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, domestic violence has been identified as a predictor of depression ( 35 ). Moreover, emotional exhaustion has been higher in women than men during the COVID-19 pandemic ( 32 , 36 , 37 ), which has been directly associated with the increase or onset of depression ( 38 ). In addition, the mental health status of women in Latin America depends on several social determinants: unequal access to education and work and their benefits, as well as exposure to violence and lack of adequate reproductive health, which affect their psychological well-being ( 39–41 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the 19-25 and 36-45 age groups reported significant associations with depression. A published study from China confirmed that the young adult group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) suffered from mental health issues (Qiu et al, 2020). 13 A study published in Spain demonstrated a similar finding of high depression and stress in young adults 18-33 years old (Jiménez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study's cut-off scores were derived from Lovibond and Lovibond (1995). After multiplying each subscale by 2, the results were categorized as follows: depression-normal (0−9), mild (10−13), moderate (14−20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (≥28); anxiety-normal (0−7), mild (8−9), moderate (10−14), severe (15)(16)(17)(18)(19) and extremely severe (≥20); and stress-normal (0−14), mild (15−18), moderate (19−25), severe (26)(27)(28)(29)(30)(31)(32)(33) and highly severe (≥34). Summed scores of 10 and above indicated depression, eight and above marked anxiety, and 15 and above labeled it as stress.…”
Section: Discussionmentioning
confidence: 99%
“…Periods of self-isolation in a pandemic situation were associated with considerably increased levels of stress, anxiety, and depression, which represent internal conditions that directly and adversely affect the general well-being of an individual (Makarova & Tsvetkova, 2020;Almondes et al, 2021;Nash, 2021). For example, a study of emotional exhaustion in Chilean students during the pandemic showed that 15 % of students had serious mental health problems; moderate depression increased from 17.7 % to 20.7 %, severe depression increased by 5.2%, severe anxiety increased from 16.7 % to 26.4 %, and severe stress increased from 9.4 % to 15.9 % (Martinez-Libano, Yeomans, & Oyanedel, 2022). Emotional exhaustion refers to a situation that negatively affects an individual's life and that is characterized by a considerable decrease in psychological well-being (Chertovikova, 2018;Eidel'man, 2016;Hendriksen et al, 2021;López-Valenciano, Suárez-Iglesias, Sanchez-Lastra, & Ayán, 2021).…”
Section: Introductionmentioning
confidence: 99%